2017
DOI: 10.3390/en10122031
|View full text |Cite
|
Sign up to set email alerts
|

South Korean Household’s Willingness to Pay for Replacing Coal with Natural Gas? A View from CO2 Emissions Reduction

Abstract: Abstract:Coal is currently a major electric power generation source in South Korea when considering that forty-three percent of electricity that was generated during the first quarter of 2017 came from coal. The amount of CO 2 emissions from coal-fired power plant is two times larger than that from natural gas (NG)-fired power plant in the country. In this regard, the Korean government is trying to replace some amount of coal that is used for generation with NG to reduce CO 2 emissions. However, the cost of NG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Similarly, consumers' WTP price premium for a RE100 smartphone can be elicited through the application of the CV method. The use of the CV technique is conceptually correct in the measurement of economic benefits [6,[13][14][15]. The CV method directly asks respondents to determine their WTP contingent on a proposed situation.…”
Section: Method: CV Approachmentioning
confidence: 99%
“…Similarly, consumers' WTP price premium for a RE100 smartphone can be elicited through the application of the CV method. The use of the CV technique is conceptually correct in the measurement of economic benefits [6,[13][14][15]. The CV method directly asks respondents to determine their WTP contingent on a proposed situation.…”
Section: Method: CV Approachmentioning
confidence: 99%
“…In the literature, a number of studies dealt with the additional WTP or price premium in the area of energy [15][16][17][18][19][20][21][22]. These studies analyzed consumers' WTP and found that consumers determine their preference in an ethical and environmentally friendly way in order to mitigate greenhouse gas and air pollutants emissions or to protect the environment.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…There have been many case studies where price premium has been examined for the use of renewable energy-based electricity in place of fossil fuels-based electricity, since renewable energy has been mainly used for electricity generation [15][16][17][18]. In addition, the price premium for electricity from a non-distributed generation source over that from distributed generation source [19]; the price premium for electricity that is generated without emitting thermal discharge water over that with emitting thermal discharge water [20]; the price premium for electricity from coal-fired power plant over that natural gas-fired power plant [21]; and, price premium for eco-friendly goods over conventional goods were analyzed [22] in the literature.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 2 more Smart Citations